The Armed Word in The Fiction About the Paraguay War - de Barros de Albuquerque, Adenilson (Revista de Historia Social y de las Mentalidades, 2023)
Based on the theoretical contributions of Latin American experts (Assunção 2012; Baratta, 2014; Brezzo, 2003; Doratioto, 2002; Maestri, 2017; O’Leary, 1929; Salles, 1990; Aínsa, 1991; Fleck, 2017; Pons, 1996), interested in historical and literary issues, we analyze how historical novels related to the theme of the Paraguayan War (1864-1870). Utilizing a bipartite stance that we call “armed word”, we argue that the novels first rely on one or more of the historiographical trends about the war and, finally, it is constituted as fictional resonance organized in trenches, whether patriotic, revisionist or allegedly objective.
Keywords: Latin America; Historical Novel; Historiography; Literature